Probabilistic Seismic and Tsunami Hazard Analysis Conditioned on a Megathrust Rupture of the Cascadia Subduction Zone - Park, Hyoungsu; Cox, Daniel T.; Alam, Mohammad Shafiqual; Barbosa, Andre R. (Frontiers in Built Environment, 2017)
This paper presents a methodology for probabilistic hazard assessment for the multi-hazard seismic and tsunami phenomena [probabilistic seismic and tsunami hazard analysis (PSTHA)]. For this work, a full-rupture event along the Cascadia subduction zone is considered and the methodology is applied to a study area of Seaside, Oregon, which is located on the US Pacific Northwest coast. In this work, the annual exceedance probabilities (AEPs) of the tsunami intensity measures (IMs) are shown to be qualitatively dissimilar to the IMs of the seismic ground motion in the study area. Specifically, the spatial gradients for the tsunami IM are much stronger across the length scale of the study area owing to the physical differences of wave propagation and energy dissipation of the two mechanisms. Example results of probabilistic seismic hazard analysis and probabilistic tsunami hazard analysis are shown for three observation points in the study area of Seaside. For the seismic hazard, the joint mean annual rate of exceedance of IMs shows similar trends for the three observation points, even though for a given observation point there is a large scatter between two ground-motion IMs analyzed, which were peak ground acceleration (PGA) and spectral acceleration at a period of vibration of 0.3 s, i.e., PGA and Sa (T1 = 0.3 s). For the tsunami hazard, the joint AEP of maximum flow depth (hmax) and maximum momentum flux ((MF)max) shows a high correlation between the two IMs in the study area. The joint AEP at each of the three observation points follows a particular Froude number (Fr) due to the local site-specific conditions rather than the distributions of fault slip distributions used to generate the scenarios that are the basis of the AEP maps developed. The joint probability distribution of hmax and (MF)max throughout the study region falls between 0.1 ≤ Fr < 1.0 (i.e., the flow is subcritical), regardless of return interval (500-, 1,000-, and 2,500-year). However, the peak of the joint probability distribution with respect to hmax and (MF)max varies with the return interval, and the largest values of hmax and (MF)max were observed with the highest return intervals (2,500 years) as would be expected. The results of the PSTHA can be the basis for a probabilistic multi-hazard damage and loss assessment and help to evaluate the uncertainties of the multi-hazard assessments.